Information of the Ninth Republican Conference of the Mathematicians of Lithuanian SSR / Information of the Third Baltic Conference on geometry / Chronicle /Abstracts - Journal , Lithuanian Mathematical (Lithuanian Mathematical Journal, 1969)
Информация о девятой республиканской конференции математиков Литовской ССР / Информация о третьей прибалтийской геометрической конференции /Хроника семинаров математического общества /Рефераты Informacija apie Devintąją respublikinę Lietuvos TSR matematikų konferenciją / Informacija apie Trečiąją Pabaltijo geometrų konferenciją / Kronika / Referatai